Bahan kemoterapeutik sebagai pengontrol plak dan gingivitis - Asdar Asdar (DiscoverSys Inc., 2007)
Plaque control is one of the key elements in dental practice. The proper plaque controlfacilitates the health return for patients with gingival and periodontal deseases. Theconcept of using chemical agents to treat such conditions in the mouth has been widelyaccepted as part of dental practice for hundred of years. Chemotherapeutic agents forlocal use in the oral cavity are available in many forms over the years. The variousproduct categories and criteria for dental practice are reviewed, and consumer selectionsare suggested. To date, two agents have been accepted by The American DentalAssociation (ADA) for treatment of gingivitis: chlorhexidine mouthwash and essential oilmouthwash.